PENGARUH STRUKTUR DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Tanggor Sihombing; Annisa Larasati (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study examines the influence of the board of commissioners, audit committee, and audit quality on financial statement integrity, and further examines whether audit quality moderates these relationships. The research focuses on 45 capital goods sector companies listed on the Indonesia Stock Exchange during the 2020– 2024 period, resulting in 225 firm-year observations selected through purposive sampling. Multiple linear regression analysis was conducted using SPSS version 31 to test the proposed hypotheses. The findings reveal that both independent commissioners and audit committees exert a significant positive effect on financial statement integrity, indicating that stronger internal governance is associated with higher reporting reliability. In contrast, audit quality does not significantly affect financial statement integrity when examined directly. However, audit quality is found to strengthen the relationship between independent commissioners and financial statement integrity, although it does not enhance the influence of audit committees. These results highlight that financial statement integrity is shaped not only by external audit quality but also by the effectiveness of internal oversight mechanisms. The study emphasizes the importance of improving the competence, independence, and governance roles of both the board of commissioners and the audit committee in supporting high-quality financial reporting.